Examining the Linkage of Academic Performance and Attention by Uddin’s Numeral Finding and Typo Revealing Tests: A Cross-Sectional Pilot Study in Undergraduate Students of Bangladesh - Alam, Md. Assadik; Uddin, Md. Sahab; Uddin, G.M. Sala; Swapna, Farzana Yasmin; Amran, Md. Shah (Journal of Intellectual Disability - Diagnosis and Treatment, 2018)
Background: Attention is the state of applying the concentration to something and it’s strongly linked to academic performance. The drive of this study was to analyze the academic performance and attention of undergraduate students. Methods: The study was implemented on 139 undergraduate students of Bangladesh selected from 9 universities from April to August 2018. In this study to investigate the attention of the students, the Uddin’s Numeral Finding (NF) and Typo Revealing (TR) tests were used. Results: In the NF test male students with last semester cumulative grade point average (CGPA) of 3.47 (highest) exerted the maximum 40% attention but female students exerted only 33.3% attention and their last semester CGPA was 3. Students with age > 22 years exerted maximum, 70.55%, and 35.2% attention in NF and TR tests respectively with last semester CGPA of 3.56 (maximum). In the NF and TR tests, highest, 89.73%, and 50.33% attention respectively were reported by 1st-year students with last semester CGPA of only 3.70. High-socioeconomic status students with last semester CGPA of 3.43 (lowest) exerted maximum 75.30% attention in NF test. There were no significant associations between variables. Conclusion: Attention is a very rudimentary function that often is a forerunner to cognitive functions. Individual differences in academic performance have been linked to differences in attention and intelligence.